TRIM25 promotes the cell survival and growth of hepatocellular carcinoma through targeting Keap1-Nrf2 pathway - Yanfeng Liu (Nature Portfolio, 2020)
The unfolded protein response allows tumour cells to adapt to ER stress, and aberrant activation of Nrf2 confers cancer progression. Here, the authors show that TRIM25 is induced during ER stress and promotes tumour cell survival by targeting Keap1 for degradation, leading to Nrf2 activation.